A history of the expansion of Christianity ; v. 3 three centuries of advance, A.D. 1500-A.D. 1800 - Latourette, Kenneth Scott 1884-1968 (Exeter, UK Paternoster, 1971)
Includes bibliographical references and index.
First published 1939, Harper and Row, Publishers, New York.
Keywords: Church history -- Modern period, 1500-1800.